1980
DOI: 10.1104/pp.66.2.302
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Exchange in Leaves in the Light

Abstract: Photosynthetic 02 production and photorespiratory 02 uptake were measured using isotopic techniques, in the C3 species Hirschfeldia incana Lowe., Helianthus annuus L., and Phaseolus vulgaris L. At high CO2 and normal 02,02 production increased linearly with light intensity. At low 02 or low C02, 02 production was suppressed, indicating that increased concentrations of both 02 and CO2 can stimulate 02 production. At the CO2 compensation point, 02 uptake equaled 02 production over a wide range of 02 concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
138
3

Year Published

1983
1983
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(154 citation statements)
references
References 19 publications
13
138
3
Order By: Relevance
“…The evidence for the involvement of pseudocyclic electron transport in photosynthesis is based mainly on the observation of high rates of 02 uptake measured during photosynthesis at saturating CO2 in chloroplasts, cells, and leaves (6,(8)(9)(10). It is generally assumed that most of this 02 uptake is Fd-dependent and linked to ATP synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence for the involvement of pseudocyclic electron transport in photosynthesis is based mainly on the observation of high rates of 02 uptake measured during photosynthesis at saturating CO2 in chloroplasts, cells, and leaves (6,(8)(9)(10). It is generally assumed that most of this 02 uptake is Fd-dependent and linked to ATP synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of 02 uptake have been measured in thylakoid preparations from spinach leaves in the presence of high concentrations of Fd (1; R. T. Furbank and M. R. Badger, unpublished), during photosynthesis in intact chloroplasts and cells (8,9), and in leaves of C3 plants (6,10). The values of 02 uptake measured in these studies are comparable to and, in several cases, exceeded the value (1 1.3% of total 02 evolution) required for the generation of all the extra ATP needed for CO2 fixation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is analogous to the induction period of photosynthesis (Marsho et al, 1979 ;Foyer et al, 1992). Although it has frequently been considered that high light intensities promote higher rates of O # reduction (Canvin et al, 1980 ;Badger, 1985 ;Grace & Logan, 1996), it has also been suggested that O # reduction accounts for a greater proportion of electron flow at low light intensities (Heber et al, 1978). If electrons do leak to O # at a fixed proportion of overall electron transport rates, then absolute rates of O # reduction will obviously increase with light intensity but will not increase further at light intensities above those saturating for photosynthesis (see an analogous discussion of photorespiration in section V(3)).…”
Section: The Role Of Oxygen In Atp Synthesismentioning
confidence: 99%
“…In many cases, concentrations of CO # intended to eliminate photorespiration have probably not been sufficiently high, and it is likely that ongoing lightdependent O # uptake at these ' high ' CO # concentrations mainly reflects continuing photorespiration (Canvin et al, 1980 ;Osmond & Grace, 1995). A complementary approach has exploited transformed plants with greatly decreased Rubisco activities (Ruuska et al, 2000).…”
Section: The Role Of Oxygen In Atp Synthesismentioning
confidence: 99%